Perancangan Media Sosial Instagram Sebagai Media Promosi Wisata Kuliner Karesidenan Bojonegoro - Ikhsan, Tsari Rifdah Tsani; Sarjono, Sarjono (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2024)
Bojonegoro Residency is an area that is often passed by migrants. However, there is a problem that newcomers don't know where to stop and choose food according to their taste. Bojonegoro residency district has a variety of delicious culinary delights and souvenirs that you may not find in other cities. For this reason, the social media designer Instagram was used as a promotional medium for Bojonegoro residency culinary tourism which includes food illustrations, descriptions and additional information for each culinary tourism destination. The design method uses the Sanyoto (2006) design model, with stages of background, identification, company and product data, marketing data, analysis, synthesis, design concept, design concept, and final design. The production process is carried out through creating idea layouts and rough layouts manually, complete layouts digitally and finishing. From this research, the main media were produced in the form of Instagram feeds and exhibition supporting media including banners, posters, infographics, pamphlets, leaflet brochures, digital catalogues, websites, social media advertising displays and tote bag merchandise.